Reviewing the narrative concerning the impact of population growth in Africa - Mensah, Cocou Marius (Lexonomica, 2019)
This article discusses the topic of population growth in Africa, a recurring theme in the era of climate change and the fight against CO2 emissions. The African continent is full of essential raw materials and encompasses the youngest population in the world. There is no doubt concerning the significant role it will play in global affairs, at a time when the world population is ageing, according to the UN statistics. In recent years, many policymakers have highlighted the necessity to deal with overpopulation, provoking moral controversial and basic human rights abuses. This article, however, proposes an opposite argumentation based on fresh data and emphasises the opportunities and challenges to take on, as the author considers "overpopulation" as more of a challenge than a sentence to underdevelopment. Though the paper mentions different issues linked to overpopulation, such as migration crisis, ecological sustainability and the UN Sustainable Development Goals, it concludes with a reminder of the importance of international cooperation as a solution to global issues.
Keywords: African Union; Afrika; demografija; demografski razvoj; ekologija; environmental footprint; European Union; global issues; impact of population growth; international cooperation; migration trends; pollution; prebivalstvo; UN sustainable development goals